Le revenu annuel garanti : nouvelle forme de sécurité du revenu - Bellerose, Pierre-Paul (L'Actualité économique, 1974)
AbstractThis paper discusses guaranteed annual income (GAI) as a mean of income redistribution and an alternative to current income security programs, with an emphasis on some basic facts commonly overlooked in recent debates.In the first part, GAI is shown to be, conceptually and technically, a logical evolution rather than a revolution considering the current income security program.In the second part, we show that the cost of income security programs must essentially be related to the amount of "net transfers". As a consequence, GAI programs will be costlier than the present system, because they require greater net transfers.In the third part, given a distribution of families by level of income, we show that the rate of decrease of poverty through any GAI program depends on the relative values of both the arbitrarily chosen poverty threshold and on the selected breaking point of "zero net transfer". Finally, rules are established pertaining to the effect of various GAI programs on poverty.